Asian business and management: review and future directions - Fabian Jintae Froese; Ashish Malik; Satish Kumar; Saumyaranjan Sahoo (Asian Business & Management, 2022)
This century has been proclaimed the Asian century, as industrialised countries such as Japan, Singapore, and South Korea, along with rapidly emerging nations such China and India, have contributed to worldwide economic growth. In response, research has analysed the reasons why Asian business and management have found such success. Based on a bibliometric analysis of Asian Business & Management (ABM), a premier journal devoted to Asian management, here we examine the performance of the research constituents, social structure, and intellectual structure of 331 scholarly papers, which sheds light on the growing influence of ABM through six major knowledge clusters: corporate social responsibility; business management in emerging markets; corporate governance; internationalization; political and business ties; and organization culture and performance. Temporal analysis reveals the emergence of strategy and human resource management as a distinct knowledge cluster and the increasing importance of China as a research context and producer. Based on this analysis, we propose future research directions.
Keywords: 650; Bibliometrics; Review; Bibliometric analysis; Asian business and management